Prevalence Of Helmint Infection In Cat’s Feces In Surabaya City: Prevalensi Infeksi Helmin Pada Feses Kucing Di Kota Surabaya - Rohmayani, Vella; Arimurti, Anindita Riesti Retno; Romadhon, Nurhidayatullah; Lihabi, Lihabi (Medicra (Journal of Medical Laboratory Science/Technology), 2023)
Cats are one of the most popular animals because of their cute and tame appearance. Just like other organism, cats can become infected worms if they are not kept clean. Cats infected with worms will initially lose their appetite, over time they will lose weight. Cats infected with worms, if kept and not treated continuously, can transmit to cat owners (humans). This study aims to determine the prevalence of parasitic worm infection in cat feces in the city of Surabaya, and to compare the prevalence of parasitic worm infection in domesticated cats with cats living wild in the city of Surabaya. The samples used in this study were 100 faecal samples, which were taken from 50 cats that live in the wild and from 50 live cats that are kept. Examination of faecal samples was carried out directly and indirectly using the saturated NaCl debris method, the data obtained will be presented descriptively and analyzed using the Chi-square test. Based on the results of the research conducted, the prevalence of worm infection in feral cat feces was 60%, while in domestic cats the prevalence was 10%. The types of worms that were found were Toxocara spp., Ancylostoma spp., Diphyllobothrium spp., and Trichuris spp. Based on the Chi-square test, it can be concluded that there is a significant relationship (P<0.05) between the prevalence of parasitic worm infection in domesticated cats and cats that live in the wild.